(untitled) (The Journal of Medicine, Humanity and Media, 2024)
Associate Professor Younbo Jung’s lecture on "Interdisciplinary Empirical Research on Social Aging and Health Communication" explores the intersection of technology, aging, and health. Jung discusses the impact of industrial revolutions on social aging, highlighting the increasing global life expectancy and the potential of "Gerontechnology" in addressing challenges faced by aging societies. He introduces AB testing as a crucial research methodology, demonstrating its application in optimizing decision-making processes. Jung presents his research findings, including a study on how electronic games can reduce loneliness among the elderly, and another comparing the effectiveness of video versus VR teaching for older adults. The latter reveals VR’s superior ability to generate pleasure and positively influence perceived usefulness and future usage intentions. Jung concludes by emphasizing older adults’ enthusiasm for learning new technologies, with pleasure being a key factor in their positive learning experiences. This lecture underscores the importance of interdisciplinary approaches in addressing the complex issues surrounding social aging and health communication in the digital age.